2017
DOI: 10.1080/15389588.2017.1326595
|View full text |Cite
|
Sign up to set email alerts
|

Acute impairing effects of morphine related to driving: A systematic review of experimental studies to define blood morphine concentrations related to impairment in opioid-naïve subjects

Abstract: A plasma morphine concentration of 50 nmol/L (approximately 14.3 ng/mL) could represent an upper level, under which there is little accompanying road traffic risk. A single dose of 5 mg morphine IV and analgetic equivalence doses of fentanyl, hydromorphone, oxycodone, and oxymorphone are presented with the suggestion that few traffic-relevant effects will appear after such doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…When morphine is administered, the diminished pain sensation may reduce the level of activation of the SN, which potentially leads to an attenuation of the DMN deactivation. Second, opioids such as morphine are known to impair cognitive functions (Strand et al, 2017 ). This may be carried out by altering the fronto-parietal and medio-lateral connectivity of the brain cognitive networks (Hudetz, 2012 ; Khalili-Mahani et al, 2012 ), including the DMN which has been seen to be important in the maintenance of a subject’s cognitive performance (Eichele et al, 2008 ; Prado and Weissman, 2011 ; Lin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…When morphine is administered, the diminished pain sensation may reduce the level of activation of the SN, which potentially leads to an attenuation of the DMN deactivation. Second, opioids such as morphine are known to impair cognitive functions (Strand et al, 2017 ). This may be carried out by altering the fronto-parietal and medio-lateral connectivity of the brain cognitive networks (Hudetz, 2012 ; Khalili-Mahani et al, 2012 ), including the DMN which has been seen to be important in the maintenance of a subject’s cognitive performance (Eichele et al, 2008 ; Prado and Weissman, 2011 ; Lin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As Figure 2 (left panel) shows, most performance impairments have been reported in studies using high doses of opioid agonists only, although some studies have observed performance decrements at medium doses (of hydrocodone, oxycodone and partial agonists). This suggests that the effect on opioid agonists on coding performance might be dose-related, although a clear link between plasma morphine concentrations and DSST impairments is currently lacking (Strand, Arnestad, Fjeld, & Mørland, 2017).…”
Section: Coding Taskmentioning
confidence: 99%
“…As Figure 3 (left panel) shows, most performance impairments have been reported in studies using high doses of opioid agonists only, although some studies have observed performance decrements at medium doses (e.g., hydrocodone, oxycodone, and partial agonists). This suggests that the effect of opioid agonists on coding performance might be dose-related, even though a clear link between plasma concentrations and DSST impairments is currently lacking (Strand, Arnestad, Fjeld, & Mørland, 2017).…”
Section: Review Of Studies On Cognitive Controlmentioning
confidence: 99%